The budget of nitrogen in the grow-out of the Amazon river prawn (Macrobrachium amazonicum Heller) and tambaqui (Colossoma macropomum Cuvier) farmed in monoculture and in integrated multitrophic aquaculture systems - Flickinger, Dallas L. [UNESP]; Costa, Gelcirene A. [UNESP]; P. Dantas, Daniela [UNESP]; Moraes-Valenti, Patricia [UNESP]; Valenti, Wagner C. [UNESP] (Hindawi, 2019)
This work determined the nitrogen inputs, outputs and accumulation in compartments of stagnant earthen ponds for the monoculture and integrated multi-trophic aquaculture (IMTA) of the Amazon river prawn (Macrobrachium amazonicum) and tambaqui (Colossoma macropomum), using recycled hypereutrophic water. A completely randomized experiment was designed with four treatments and three replications: PM–monoculture with 30 prawns/m2, FM - monoculture with 3 fish/m2, IMTA - polyculture with 30 prawns/m2 and 30 fish/m2 free, POLY-CAGE - polyculture with 30 prawns/m2 free and 40 fish/m3 in net-cages. Animals, rain, water, feed, soil, gas, accumulated sludge, and suspended sediments were collected throughout the experiment to determine their nitrogen contents and to calculate the nitrogen budget. Results showed that much of the nitrogen available escapes to atmosphere as N2 (~40%–56%) after denitrification or accumulated within bottom sludge (~14%–42%). The remaining nitrogen was converted in animal biomass (~5%–21%) or was discharged to receiving waterbodies in the outlet water (~11%–13%). Feed management appeared to influence the major biological processes in the aquatic nitrogen cycle, such as photosynthesis and denitrification. The fish-prawn IMTA systems converted approximately 53%–75% of feed nitrogen into harvestable products, which is more efficient than the 19%–46% of feed nitrogen converted in the monocultures. However, a large amount of nitrogen is accumulated in the pond bottom in all systems. An increased prawn density or the addition of a mud-feeder species to the culture may enhance the incorporation of this material in harvested biomass, improving the efficiency of the systems.
Keywords: biomitigation; earthen ponds; mass balance; positive aquaculture impacts; Sustainability